2015
DOI: 10.1021/nl503933n
|View full text |Cite
|
Sign up to set email alerts
|

Linearly Polarized Emission from an Embedded Quantum Dot Using Nanowire Morphology Control

Abstract: GaAs nanowires with elongated cross sections are formed using a catalyst-free growth technique. This is achieved by patterning elongated nanoscale openings within a silicon dioxide growth mask on a (111)B GaAs substrate. It is observed that MOVPE-grown vertical nanowires with cross section elongated in the [21̅1̅] and [1̅12] directions remain faithful to the geometry of the openings. An InGaAs quantum dot with weak radial confinement is realized within each nanowire by briefly introducing indium into the react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 14 publications
2
37
0
Order By: Relevance
“…Next, it is beneficial to examine the catalyst-free anisotropically cross-sectioned GaAs NWs reported by Foster et al ., under these theoretical guidelines22. To realize such NWs, they have created asymmetric trench-like openings in a selective area growth mask; the trenches were aligned with various and type orientations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, it is beneficial to examine the catalyst-free anisotropically cross-sectioned GaAs NWs reported by Foster et al ., under these theoretical guidelines22. To realize such NWs, they have created asymmetric trench-like openings in a selective area growth mask; the trenches were aligned with various and type orientations.…”
Section: Resultsmentioning
confidence: 99%
“…Nanowire cross section shape and faceting is expected to influence its electrical, mechanical, optical and chemical properties18192021222324. In particular, Foster et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that the growth direction of the L-shaped structures corresponds to one of the 〈11-2〉 directions, being in agreement with the positioning of the indium droplets at the corners between two {110} facets. Interestingly the 〈11-2〉 direction is also the growth direction for which the growth of membranes and nanowires with elongated cross sections is possible in the case of GaAs in patterned silicon dioxide on GaAs(111)B [41,42].…”
Section: Resultsmentioning
confidence: 99%
“…Similar modifications of the coupling have already been demonstrated using symmetric pyramids [9], nanowires [10]- [12], ridge waveguide [13] or by resonant coupling to the electromagnetic field of micro-or nanocavity resonators [14]- [16]. In case of microcavities, the DOLP can be increased by tuning the emitter into resonance with one of the orthogonally polarized fundamental cavity modes [15].…”
Section: Introductionmentioning
confidence: 75%